Molecular Characterization of Gut Bacterial Flora of Honeybee (Apis Mellifera Adansonii) From Some Selected Apiaries in Ogun State, Nigeria - E.O. Oladipupo-Alade; O.A. Lawal; I.O. Oyewo; I.E. Odiaka; N.O. Haastrup; M.D. Oyedele; O.A. Ganiyu (Journal of Applied Sciences and Environmental Management, 2021)
Research related to physiology and pathology of honey bees in particular Apis mellifera adansonii has attracted a lot of attention. The present study is aimed to determine honeybee (Apis mellifera adansonii) gut microbiome from Apiary in Olabisi Onabanjo University and Osoba Avenue Odo-Epo, Odogbolu Local Government. Twenty (20) honeybees workers (A. mellifera) were collected into a small vile containing sugar powder from the apiary located in OOU and Osoba Avenue at Odo-Epo during rainy season in July and transported to Zoology and Environmental Biology laboratory in OOU and kept in ice-cubes (-50C) till daybreak. Standard microbiological analysis for isolation of bacteria was used, adopting Clinical Laboratory Standard Institute procedures. The phylogenetic analyses based on the 16S rDNA gene were further used to characterize the organism in order to establish  relationships among them. The results showed microbiota of the studied samples includes; Cedeca davisae, Cronobacter  dublinensis, Enterobacter aerogenes, Kluyvera cryocrescens, Klebsiella oxytoca, Providencia vermicola, Salmonella enteric, Providencia alcalifaciens, Serratia nematodiphila, Pseudomonas plecoqlossicida, Klebsiella michiganensis, Serratia marcenscens, Pseudomonas aeruginosa, Escherichia coli, Aeromonas hydrophila and Enterobacter asburiae. Klebsiella spp. was more abundant and prominent in the digestive guts of honeybee workers both in OOU and Osoba Avenue, Odo Epo. The result of the percentage identity and closest accession of the isolates revealed that, Enterobacter aerogenes had the closest accession number and with highest percentage identity of (99%). The findings from this study showed that microbiota component communities of A. mellifera adansonii in OOU were composed of more Gram-negative bacteria than Gram-positive bacteria in Odo Epo.